Keanekaragaman Kupu-Kupu (Sub Ordo Rhopalocera) pada Dua Tipe Habitat - Yulminarti Yulminarti; Suci Amelia Putri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine butterflies' species composition and species diversity in the Siabu area. The sampling method in this study used two ways, namely direct sampling using insect nets (transect count and netting) and bait traps along the transect (500 m transects in each habitat). The results showed that the number of individuals ranged from 109-114 (steppe-secondary forest) individuals and the number of species ranged from 19-52 species (pasture-secondary forest). The secondary forest has an index of species diversity and evenness of species, namely H'= 3.63 and E= 0.92 and grasslands have H'= 2.31 and E= 0.78. In conclusion, the diversity index value of the Siabu Village area is in the high category. In addition, there is one rare and protected butterfly species included in the CITES Appendix II list, namely Trogonoptera brookiana, which is found in secondary forest. Keywords: Species Diversity Index, Secondary Forest, Sub Order Rhopalocera